The toilet debate: Stalling trans possibilities and defending 'women's protected spaces'1. Issue 4 (July 2020) - Jones, Charlotte; Slater, Jen
As one of the few explicitly gender-separated spaces, the toilet has become a prominent site of conflict and a focal point for 'gender-critical' feminism. In this article we draw upon an AHRC-funded project, Around the Toilet, to reflect upon and critique trans-exclusionary and trans-hostile narratives of toilet spaces. Such narratives include ciscentric, heteronormative and gender essentialist positions within toilet research and activism which, for example, equate certain actions and bodily functions (such as menstruation) to a particular gender, decry the need for all-gender toilets, and cast suspicion upon the intentions of trans women in public toilet spaces. These include explicitly transmisogynist discourses perpetuated largely by those calling themselves 'gender-critical' feminists, but also extend to national media, right-wing populist discourses and beyond. We use Around the Toilet data to argue that access to safe and comfortable toilets plays a fundamental role in making trans lives possible. Furthermore, we contend that – whether naive, ignorant or explicitly transphobic – trans-exclusionary positions do little to improve toilet access for the majority, instead putting trans people, and others with visible markers of gender difference, at a greater risk of violence, and participating in the dangerous homogenisation of womanhood.